2015
DOI: 10.1111/1758-2229.12295
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biofilm development of Streptococcus pneumoniae and formation of choline‐binding protein–DNA complexes

Abstract: Extracellular deoxyribonucleic acid (eDNA) is an essential component of bacterial biofilm matrices, and is required in their formation and maintenance. Extracellular DNA binds to exopolysaccharides or extracellular proteins, affording biofilms greater structural integrity. Recently, we reported evidence of intercellular eDNA-LytC complexes in pneumococcal biofilms. The LytC lysozyme is a member of the choline-binding family of proteins (CBPs) located on the pneumococcal surface. The present work shows that oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 77 publications
2
22
0
2
Order By: Relevance
“…Together with our previous results3144, plus those of other authors on pneumococcal biofilms70, the present findings pave the way for detailed in vitro studies on more complex pneumococcal–NT Hi biofilms.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Together with our previous results3144, plus those of other authors on pneumococcal biofilms70, the present findings pave the way for detailed in vitro studies on more complex pneumococcal–NT Hi biofilms.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have shown that eDNA binds extracellular proteins such as PilA (the type IV pilin protein)15 and the bacterial DNABII family of proteins (also known as histone-like proteins or Hlps)43. Recent results from our laboratory have shown that the choline-binding proteins of S. pneumoniae have the unexpected capacity to strongly bind DNA through electrostatic interactions; they may therefore be important in the early stages of biofilm formation3144. This might also be true for other bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococcal autolysis can free DNA that could then contribute to biofilm formation as has been previously described (Steinmoen et al, 2002; Domenech et al, 2015). To determine if LytA is contributing to increased biofilm formation seen in the parental T4R strain, the effect of zinc on biofilm formation in a mutant strain lacking LytA (ΔLytA) was investigated.…”
Section: Resultsmentioning
confidence: 62%
“…Pneumococcus specifically has the ability to release extracellular DNA through the process of LytA-dependent autolysis (Steinmoen et al, 2002; Domenech et al, 2015). Domenech et al have published multiple studies highlighting the relationship between the choline-binding family of proteins and extracellular DNA in pneumococcal biofilms (Moscoso et al, 2006; Domenech et al, 2015). In order to investigate if LytA-dependent autolysis was contributing to our increasing biofilms in different concentrations of zinc, we utilized a mutant lacking LytA.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation results in water deficiency, limitations in nutrient transport and death during later stages of infection (Rodrigues et al, 2013). This structure is involved in the pathogenicity of several species such as X. fastidiosa (Caserta et al, 2010; Voegel et al, 2010; Janissen et al, 2015), Neisseria meningitides (Arenas et al, 2015), Streptococcus pneumonia (Domenech et al, 2015), Salmonella enteric (O'Leary et al, 2015), and Pseudomonas syringae (Chowdhury and Jagannadham, 2013), conferring resistance to antibiotics and other chemicals used to control bacterial populations.…”
Section: Introductionmentioning
confidence: 99%